Control of THz Surface Plasmons by Geometric Phases - Hu, Shulin; Wang, Peng; Zhou, Cai; Hu, Min; Xiong, Yuli; Xu, Huanhuan; Li, Xiaoyu; Xu, Mingyao; Wang, Shengxiang (Frontiers in Physics, 2021)
Surface plasmons (SPs) are expected to have a wide range of applications in many fields, so they have recently attracted much attention. However, most of the previous studies achieved the manipulation of SPs through designing the structure of the individual meta-atom. When developing the next generation of integrated photonic devices and components, it is essential to seek out new methods of software control, which enable more diverse modulation and higher efficiency. Here, the tunable emission of SPs with metasurfaces is systematically studied. SPs are a source of on-chip plasmonic vortices (PVs). To verify the controllability of the directional excitation of SPs, we designed beam deflectors with different angles of surface waves (SWs). Furthermore, PVs with different topological charges were generated by arranging spatially varied microslits. The proposed control strategy provides a common platform for various promising applications, such as on-chip generation of the propagation control of SPs and PVs.